Indigenous and Customary Land Tenure Security: History, Trends, and Challenges in the Latin American Context - Sauls, L.A.; Galeana, F.; Lawry, S. (Springer, 2022)
This chapter explores Indigenous and customary tenure regimes, considering the differing historical trends in the statutory recognition of customary tenure arrangements. Indigenous and customary land tenure regimes are dynamic, responding to changes in local-to-global socio-ecological conditions and political and market influences, as well as context-specific and based on historic socio-environmental relations. Despite trends toward legal recognition, a disconnect remains between titling or recognition and the security of these regimes. After defining Indigenous and customary land tenure regimes, we discuss their evolution from colonial encounters through the post-colonial era, on to trends in customary tenure recognition today. Finally, drawing primarily on evidence from Latin America, we explore how tenure insecurity of Indigenous and customary lands remains a significant challenge to realizing sustainable development across diverse landscapes.